PENGARUHKOMPENSASIFINANSIALDANSEMANGAT KERJA TERHADAP KINERJA KARYAWAN PADAKOPERASI SIMPAN PINJAM â€œMUHAMMADIYAHDI MARTAPURAâ€ KABUPATEN BANJAR - Abdul Kadir (LPPM University 17 Agustus 1945 Samarinda, 2021)
Abstract: The purpose of this study was to determine the effect of financial compensation and work morale on employee performance at the Savings and Loans Cooperative